Taxonomic Study on Libellulidae Species (Odonata: Anisoptera) in Al-Marj Region Libya - Zayeid, Youssef Mousa; Altaib, Altaib Noah (Al-Mukhtar Journal of Sciences, 2021)
The study was aimed to identify some species of Odonata on Al-Marj area in Aljabal Alakder. The study carried out from January 2018 to December 2019 in Al Jabal Al Akhdar region which aimed to identify the species of the suborder Anisoptera, family Libellulidae in twelve sites. Four species of this family were recorded, Crocothemis erythraea (Brulle, 1832), Orthetrum anceps (Schneider, 1845), Sympetrum fonscolombii (Selys, 1840), and Trithemis arteriosa (Burmeister, 1839), endemic to the study area. Their identification was based on the external morphology of the adults.